Electromagnetic Response of Layered Dielectric Structures to Pulsed Acoustical Action; Russian Physics Journal; Vol. 58, iss. 4 - Bespalko (Bespal'ko) A. A. Anatoly Alekseevich; Lyukshin B. A. Boris Aleksandrovich; Utsyn G. E. Grigory Evgenjevich; Yavorovich L. V. Ludmila Vasilievna (2015, 2015)
Title screen